smurfy14
  • smurfy14
I need help on how to solve this problem and how to set it up. 3^(3x-1)=9(x-3)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
smurfy14
  • smurfy14
Typo on last post it should be: 3^(3x-1)=9^(x-3)
anonymous
  • anonymous
first u note that 9^(x-3) = 3^[2(x-3)] therefore; 3x-1=2(x-3). solve this to get x.
smurfy14
  • smurfy14
where did the two come from?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
thats because 3^2=9
anonymous
  • anonymous
as example, 9^2=3^(2*2)=81. thats the same i done above. but instead of integer, the power in the question is an equation.
smurfy14
  • smurfy14
ok so if i have a problem like 3^(4x-2)=27^(x) then it would be 4x-2=3(x)??
anonymous
  • anonymous
yup. u got it right.
smurfy14
  • smurfy14
now what if i got a^(x-4)=[a^6][a^(3x-6)]
anonymous
  • anonymous
let say u hav (2^3)*(2^5), this wil be equal to 2^(3+5) so in ur case, [a^6][a^(3x-6)]=a^[6+(3x-6)]
smurfy14
  • smurfy14
so then you would do a^x-4=a^[6+(3x-6)] and then what do you do next?
anonymous
  • anonymous
yup.then do same as before, equate the power to get the x. x-4=6+(3x-6)
smurfy14
  • smurfy14
alright now if you have a problem 9^(2x+1)=27^(x+2) then you have 2x+1=???
anonymous
  • anonymous
in this case, first u need to make the "base" equal. note that 9=3^2 and 27=3^3. therefore,the eqn become: 3^[2(2x+1)]=3^[3(x+2)] then equate the power as usual: 2(2x+1)=3(x+2)
smurfy14
  • smurfy14
ok so now i have 5^(2x+3)=(square root of 5)^(x+4)
anonymous
  • anonymous
u can write square root of 5 as 5^(1/2) then u can proceed with 2x+3= (1/2)*(x+4)
smurfy14
  • smurfy14
why do you write it as 1/2? how did you get that
anonymous
  • anonymous
dont have to calculate anything for that. its basic rule how to write it a square root. \[\sqrt[m]{A} = A ^{1/m}\]
smurfy14
  • smurfy14
ohh ok haha also, i have (2a)^x=(4a^2)^x+2 and so would it be x=2(x+2)?
anonymous
  • anonymous
yes.thats right.
anonymous
  • anonymous
if the ratio of snicker to m&m's is 5 to 6 then the store could have
anonymous
  • anonymous
help
smurfy14
  • smurfy14
and on the last problem with the 1/2... what would the answer be?
anonymous
  • anonymous
i think it is x=-2/3. u got the same?
anonymous
  • anonymous
can u help me on my pro
smurfy14
  • smurfy14
no i got something different :/ umm i guess i did it wrong because i think you are right
anonymous
  • anonymous
try check it again. maybe a careless mistake.
smurfy14
  • smurfy14
ok now i got it :) okay well to switch gears a bit.. now i have to do log(3/5)(25/9)=x+4 **3/5 is the little bottom number**
anonymous
  • anonymous
remember that if \[\log_{a} b = c \] this implies\[a ^{c}=b\] so, u hav to change the initial problem into the 2nd form. and u also hav to note that 25/9= (3/5)^-2
smurfy14
  • smurfy14
you mean 5/3^-2?
anonymous
  • anonymous
no. 25/9= (5/3)^2 = (3/5)^-2
smurfy14
  • smurfy14
ohh ok! im sorry to be asking so many questions its just that im so confused! ok on 2^x * 4^(x+5)=4^(2x-1) what do you do next?
anonymous
  • anonymous
since 4=2^2, then the eqn becomes; 2^x * 2^[2(x+5)]=2^[2(2x-1)] this implies; 2^[x+2(x+5)]=2^[2(2x-1)] therefore, x+2(x+5)=2(2x-1)
smurfy14
  • smurfy14
ohh ok umm what did you get on the previous problem? i dont know where x is supposed to go when you solve. i got this: (3/5)^4=(3/5)^-2
anonymous
  • anonymous
it should be (3/5)^(x+4)=(3/5)^-2 x included in "c" based on the general form i gave u before.
anonymous
  • anonymous
im going to bed.sorry cant help more.good luck with the problems..
smurfy14
  • smurfy14
ohh i forgot the x! so it should be -6.
smurfy14
  • smurfy14
ok thanks for all your help!!!! :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.